Investigating the Utilization of YouTube Videos for Improving Speaking Proficiency in English - Mulyo, Suratno; Rokhayati, Titi; Setiyono, Junaedi (Scripta : English Department Journal, 2024)
This study conducts a systematic literature review to examine the efficacy of incorporating YouTube videos to improve the speaking abilities of English as a Foreign Language (EFL) learners. From 2022 to 2023, the study thoroughly examines, assesses, and combines 30 pertinent publications. By applying strict criteria for inclusion, the evaluation focuses on three specific publications that examine the influence of YouTube videos on speaking proficiency. The findings emphasize the favourable results regarding motivation, student engagement, instructional methods, and the diverse advantages of YouTube in various educational settings. The debate highlights the various benefits observed in rural schools and among public administration students, demonstrating the potential of YouTube to enhance vocabulary, pronunciation, and general language proficiency. The study emphasizes the significance of YouTube in offering authentic language exposure, promoting community growth, and leading to favorable outcomes in English proficiency.